Participatory Action Research on Climate Risk Management, Bangladesh - Braun, M.; Saroar M (WorldFish, 2012)
The rural populations of southern Bangladesh are some of the most vulnerable communities in the world to the future impacts of climate change. They are particularly at risk from floods, waterlogged soils, and increasing salinity of both land and water. The objective of this project was to analyze the vulnerability of people in four villages that are experiencing different levels of soil salinity. The study evaluated the strengths and weaknesses of current coping strategies and assessed the potential of an index-based insurance scheme, designed diversification and better information products to improve adaptive capacity. Participatory research appraisal was carried out in rural communities with local stakeholders in the districts of Jhalokati, Bagerhat, Khulna and Satkhira. The village in Jhalokati is not yet affected by salinity, the village in Bagerhat is marginally affected, whereas the villages in Khulna and Satkhira are exposed to relatively high levels of salinity in both the soil and the water. The methods used included risk prioritization matrices, semi-structured interviews and focus group discussions. The analyses were gender differentiated. The results allowed for an assessment of risks, exposure, adaptive capacity and the perceived needs of people in these communities. The study provides a baseline for future interventions and recommends activities for the CG’s Climate Change, Agriculture and Food Security program for 2012 and beyond.